Responsibility Accounting on Amil Zakat Organization - Irda Agustin Kustiwi; Tjiptohadi Sawarjuwono (Universitas Padjadjaran, 2021)
Responsibility accounting carried out by organizations in the business sector is based more on material budgets. This budget is in the form of accumulated costs at the responsibility center that is used to assess management performance. Islam explains that accountability based on al-Mishbah's interpretation has a broad essence. Responsibility accounting includes the relationship between humans and humans (material), environmental (social), and Creator (spiritual). This research uses a qualitative method with an exploratory case study approach. The case study approach was chosen because the context of accountability accounting is an important understanding related to phenomena that occur in the field. The exploratory type case study approach was chosen with the aim of the researcher to reconstruct the existing accounting responsibility in Nurul Hayat Surabaya in accordance with the terminology at the Al Mishbah interpretation. The results obtained that Nurul Hayat Surabaya has a vertical relationship to the Creator, horizontal to direct stakeholders and indirect stakeholders, as well as a commitment that is in line with the four characteristics of Rasullullah. So according to the thought of the accounting accountability reconstruction researchers, what happened could be that in Nurul Hayat Surabaya, it could be in accordance with al-Mishbah's interpretation of tijarah. Responsibility accounting is material, social and spiritual.